P-048 Co-Existing IBS in Inflammatory Bowel Disease (IBD) Is Associated with Increased Risk of Chronic Fatigue (CF), Especially in Females. (February 2017) - Bernklev, Tomm; Huppertz-Hauss, Gert; Opheim, Randi; Henriksen, Magne; Lie Høivik, Marte; Moum, Bjørn; Jelsness-Jørgensen, Lars-Petter
Abstract : Background: One out of 4 IBD patients report chronic fatigue (CF) in outpatient materials, and disease activity seems to influence the prevalence of CF in a subset of patients. 1 IBS-like symptoms is another, debilitating factor in IBD patients. The primary aim of the present study was to investigate the impact of IBS-like symptoms on the prevalence of CF in IBD and further to identify possible prognostic factors for CF. Methods: The 20 years follow-up of the IBSEN (Inflammatory bowel South-East Norway) cohort was completed in 2014. A total of 599 patients with confirmed IBD diagnosis and still alive were invited to the follow-up. Of these, 129 had moved, were lost to follow-up or refused participation, leaving 470 participants in the study. In addition to interview, clinical examination and lab work-up the patients completed, the IBS symptom score (Rome-III criteria and the Chronic Fatigue Questionnaire (FQ). FQ consists of 11 questions, each asking if there is less of a problem than usual ranging from minimum 0 (no more than usual) to 3 (much more than usual), total score range is 0 to 33. The same questions can be dichotomized (0 or 1), and a score of 4 or above combined with a symptom duration of 6 months or more is defined as chronic fatigue (CF). The definition of remission of IBD was fecal calprotectin value below 250 μg/kg 2 . Results: Of the 470 included patients, we obtained calprotectin data from 344, and 77% (264/344) of these patients were in clinical remission and completed both questionnaires (FQ and Rome-III). Mean age was 55.12 (range 29–94), F/M 140/124 and UC/CD 182/82, mean disease duration 19 years. Twenty-six percentages (68/264) of these reported IBS like symptoms. Among IBS positive patients, 37% (25/68) reported CF, 33% in UC and 44% in CD patients (NS). Significantly more females than males with IBS-like symptoms reported CF, 44% versus 33%, ( P = 0.03). In IBS negative patients, merely 15% (29/196) reported CF, which is significantly lower than in the IBS positive group ( P < 0.0001). In comparison, the prevalence of CF in the Norwegian background population aged 50 to 59 years is 12.2% in males and 10.5% in females. In a logistic regression analysis with the combination of IBS and CF as dependent variable and gender and diagnosis as independent variables, female gender was statistically significant in the model, with OR = 5.3, 95% CI = 1.8 to 15.9. Conclusions: In IBD patients in remission, the presence of IBS like-symptoms was associated to an increased prevalence of CF, and far higher than comparable age groups in the background population. Female IBD patients with IBS have increased risk of CF.